Fisetin 8-C-glucoside as entry inhibitor in SARS CoV-2 infection: molecular modelling study - Mishra, Abha; Kaur, Upinder; Singh, Amit (Taylor and Francis Ltd, 2022)
Coronaviruses are RNA viruses that infect varied species including humans. TMPRSS2 is gateway for SARS CoV-2 entry into the host cell. It causes proteolytic activation of spike protein and discharge of the peptide into host cell. The TMPRSS2 inhibition could be one of the approaches to stop the viral entry, therefore, interaction pattern and binding energies for Fisetin and TMPRSS2 have been explored in the present study. TMPRSS2 peptide was used for homology modelling and then for further study.Molecular docking score and MMGBSA Binding energy of Fisetin was better than Nafamostat, a known inhibitor of TMPRSS2. Post docking MM-GBSA free energy for Fisetin and Nafamostat was 42.78 and 21.11 kcal/mol, respectively. Fisetin forms H bond with Val 25, His 41, Lys 42, Lys 45, Glu 44, Ser186.Nafamostat formed H bonds with Lys 85, Asp 90, Asp 203. RMSD plots of TMPRSS2, TMPRSS2-Fisetin and TMPRSS2-Nafamostat complex showed stable profile with very small fluctuation during entire simulation of 150 ns. Significant decrease in TMPRSS2-Fisetin and TMPRSS2 Nafamostat complex fluctu-ation occurred around His 41, Glu 44, Gly 136, Ser 186 in RMSF study. During simulation Fisetin inter-action was observed with residues Val 25, His 41, Glu 44, Lys 45, Lys 87, Gly 136, Gln 183, Ser 186 likewise interaction of Nafamostat with Lys 85, Asp 90, Asn 163, Asp 203 and Ser 205. Post simulation MM-GBSA free energy was found to be 51.87 ± 4.3 and 48.23 ± 4.39 kcal/mol for TMPRSS2 with Fisetin and Nafamostat, respectively
This paper is submitted by the author of IIT (BHU) Varanasi
Keywords: Fisetin 8-C-glucoside; Entry inhibitor in SARS CoV-2 infection; Molecular modelling study